PENGEMBANGAN TES BERBASIS HIGHER ORDER THINKING SKILL PADA PEMBELAJARAN TEMATIK KELAS V SEKOLAH DASAR - Pindia Pindia; Kartono Kartono; Tahmid Sabri (Universitas Tanjungpura, 2021)
Abstract The purpose of this research is to produce a product of testy-based Higher Order Thinking Skill on a cache of scient content. Grade v elementary school. This method of research USES this method of research. Development or reseurch and developmert (r&d) adapted. The borg and gall development model (1989). The sources of data in this study are the results of validation of the experts on test hots, of validation of linguists, and of higher order thinking skill (hots) test results (hots) of north child puda that includes: test validity analysis, test analyses, test levels of tests, and different power analyses. Research results show during the process of developing a higher order thinking skill test (hots) went through seven stages, which are potential and problem, data collecting, product design, validation design, revised design, product testing, and product revision. The worthy product of a higher order thinking skill test (hots) obtained an average value from tests worth 4.48 in highly valid categories and test compatibility aspects with materials, construction, and language came to an average of 4.42 in highly valid categories Keywords: Development, Test, HOTS , Thematic Learning.